Report from the first workshop of International Permafrost Association Action Group Rock glaciers inventories and kinematics (GeoPatterns, 2024)
The recent initiative to standardize the mapping and monitoring of rock glaciers around the world resulted in the organization of the First Workshop of the Action Group Rock glaciers inventories and kinematics, in Evolene, Switzerland. The participants focused to discuss in detail and debate several issues to be introduced in a new version of a guidelines document regarding rock glaciers inventorying. This paper discusses the development of the field trips and working sessions of the workshop.
Keywords: rock glaciers; mountain permafrost; action group; workshop; International Permafrost Association